Analysis Of Customer Interest and Satisfaction Toward BSI Mobile Banking Service - Faridha Naila Ulya; Qoyyimah Qoyyimah; Kharis Fadlullah Hana (IAIN Batusangkar, 2022)
This study aims to analyze the factors that influence customer interest and satisfaction with mobile banking services at Bank Syariah Indonesia. This study uses a descriptive qualitative research method with a phenomenological approach. Data collection technique using interviews and documentation. Data analysis using the Triangulation Technique as a validity test. The results show that the dimension of pride is a factor that influences customer interest in BSI Mobile. The sense of pride in the Mobile Banking application at Bank Syariah Indonesia is shown by the compliance with Islamic sharia principles in its performance services. Customer satisfaction with BSI Mobile is shown by the dimensions of service features which are quite complete and very satisfying for BSI Mobile users, because there are several features besides features for transactions, there are also service features to add religious knowledge such as ZISWAF channeling, juz amma and azan